Manifestation of relativistic effects in the chemical properties of nihonium and moscovium revealed by gas chromatography studies - Yakushev, A.; Khuyagbaatar, J.; Düllmann, Ch. E.; Block, M.; Cantemir, R. A.; Cox, D. M.; Dietzel, D.; Giacoppo, F.; Hrabar, Y.; Iliaš, M.; Jäger, E.; Krier, J.; et al. (Frontiers in Chemistry, 2024)
Chemical reactivity of the superheavy elements nihonium (Nh, element 113) and moscovium (Mc, element 115) has been studied by the gas-solid chromatography method using a new combined chromatography and detection setup. The Mc isotope, 288 Mc, was produced in the nuclear fusion reaction of 48 Ca ions with 243 Am targets at the GSI Helmholtzzentrum Darmstadt, Germany. After isolating 288 Mc ions in the gas-filled separator TASCA, adsorption of 288 Mc and its decay product 284 Nh on silicon oxide and gold surfaces was investigated. As a result of this work, the values of the adsorption enthalpy of Nh and Mc on the silicon oxide surface were determined for the first time, -∆ (Mc) = 54 kJ/mol and -∆ (Nh) = 58 kJ/mol (68% c.i.). The obtained ΔHads values are in good agreement with results of advanced relativistic calculations. Both elements, Nh and Mc, were shown to interact more weakly with the silicon oxide surface than their lighter homologues Tl and Bi, respectively. However, Nh and Mc turned out to be more reactive than the neighbouring closed-shell and quasi-closed-shell elements copernicium (Cn, element 112) and flerovium (Fl, element 114), respectively. The established trend is explained by the influence of strong relativistic effects on the valence atomic orbitals of these elements.